User's satisfaction on e-government services: An integrated model - Danila, Raudah; Abdullah, Akilah (Elsevier Ltd., 2014)
In many developed countries, IT (IT) adoption in government agencies has been studied extensively. Unfortunately, such study is still lacking among developing countries including Malaysia.In fact, previous studies on the adoption of e-government offer limited framework to build on further research. This study investigates citizens’ intentions and usage of e-government services and introduces a framework that combines Technology Acceptance Model (TAM), Theory of Planned Behaviour (TPB), and Information System Success (ISS) as a base to examine factors that affect the intention and usage of e-government services. The proposed e-government adoption model takes into accounts issues of personal innovativeness, perceived usefulness, perceived ease of use, attitude, subjective norm, perceived behaviour control and system quality. By investigating users of online government services, we postulate that those factors should be the predictors of continued usage of e-government services.This study has practical implications for the design of mechanisms for the adoption of e-government.